Strategi Kepala Sekolah Dalam Meningkatkan Profesionalisme Guru Di KKMTs 9 (Sembilan) Sekotong - Ahmad Ropii (Jurnal Penelitian dan Pendidikan IPS, 2022)
This research is a qualitative research using natural research methods. Data collection techniques used are Observation (Observation), interviews, Documentation. The analytical technique used in this research is qualitative naturalistic analysis. The position of the teacher as an educator requires a professional ability that is able to support the achievement of educational goals, so as to be able to create changes in behavior, both at school and in the community. Teacher professionalism can be formed through professional improvement programs. This increase is expected to be able to support teachers in carrying out their duties and roles as professional educators. The problems that occur in connection with increasing teacher professionalism in the Madrasah Tsanawiyah Working Group (KKMTs) 9 Sekotong Region are related to: weak motivation of teachers in developing their professional abilities, lack of supporting infrastructure. Increasing teacher professionalism is an effort made by the principal in increasing the effectiveness of his work. With this increase, it is expected that teachers will be able to improve the knowledge, skills and attitudes of employees in carrying out their duties as teachers. Efforts made by school principals in improving teacher